PENETAPAN HARGA KAMAR DI TRAVELODGE HOTEL KOTA BATAM - Pertiwi, Tania; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The city of Batam is a city with a geographical location that is directly neighboring to Malaysia and Singapore, thus encouraging the Riau Islands provincial government to provide various facilities and infrastructure such as hospitality. A large number of hotels make hotel management compete with each other in providing good services to their customers. In this case the Travelodge Hotel takes careful consideration so that the price set does not cause a loss for the company. This research aims to determine the pricing strategy of the rooms and to find out the methods in determining the price of rooms in the Travelodge Hotel in Batam City. Based on the method used in this research is a qualitative descriptive method to analyze the problems collected by the writer through interviews, observations, and documentation with the management of Travelodge Hotel Batam City. Based on the data analysis, the selection of strategies and methods must adjust the existing market conditions because this is very influential in determining the price of Travelodge Batam City Hotel rooms.Keywords: Price, Strategy, Method, Hotel